Asynchronized cell division in embryo‐like fossils from the Ediacaran Zhenba microfossil assemblage. Issue 6 (25th October 2022) - Zhang, Yuan; Zhang, Xingliang; Liu, Cong
Abstract: Ediacaran embryo‐like spherical fossils exhibit diverse cell adhesion patterns resembling partial cleavage‐stage embryos of living animals. Two three‐celled specimens characterized by a pair of small cells overlying a large cell have been recovered from the Ediacaran Zhenba microfossil assemblage. Their cell adhesion pattern is highly comparable to a phenomenon reported from the Weng'an biota that was interpreted as fossil embryos undergoing discoidal cleavage. However, our specimens contain fewer cells and thus probably represent developmental precursors of the Weng'an counterparts. Additionally, new material shows several anatomical features that are inconsistent with an embryo interpretation, including (1) an unusually large volume of "blastomeres, " (2) a putative nucleus preserved within the large "yolk cell, " and (3) completely separated cells. Collectively, the Zhenba embryo‐like specimens permit a reconstruction of the consecutive developmental sequence from single‐celled individuals to the three‐celled individuals, leading us to interpret the newly found specimens as products of abnormal development of Ediacaran embryo‐like organisms whose affinity remains unresolved. Abstract : The new specimens of the Ediacaran embryo‐like fossils are proposed as developmental precursors of those putative fossil embryos that utilized discoidal cleavage but are alternatively interpreted as abnormally developed individuals of problematic organisms. Highlights: Asynchronized cell division is revealed byfossils from the Ediacaran Zhenba microfossil assemblage. They are proposed as developmental precursors of those Weng'an specimens which had been interpreted as fossil embryos that utilized discoidal cleavage. They are interpreted as abnormally developed individuals of the problematic Ediacaran embryo‐like organisms.